Servqual model for the evaluation of the perceived quality of social program services - FISE in the Puno region - Inquilla-Mamani, Dr. Juan; Cutipa, Dr. Gilberto Vilca - (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The purpose of the research is to assess the level of quality perceived by users based on a "SERVQUAL Model" scale of the Social Energy Inclusion Fund (FISE) program implemented by the State in the Puno region. Method: a mixed study was carried out (quantitative - qualitative); of correlational descriptive type, in the Puno region of Peru. The statistical method SPSS v. 22, was used for processing, data processing and scientific tests. The materials used are documentary, electronic and statistical files of the program. Results: the research findings are evidenced in two aspects; First, the values of Alpha Crombach is statistically significant above 0.80, therefore, it means that the components and characteristics (attributes) analyzed allow to evaluate the quality of service offered by the FISE program. On the other hand, the analysis of the information collected through the Servqual questionnaire shows us that the variables that stand out in the user's decision process are reliability, responsiveness, security and empathy. Therefore, the service quality index (ICS) evaluated with the Servqual model is negative, the score reaches (-1.03), which indicates that users expected a better service than that received from the FISE program in the Puno region.